Encyclopedia of major marketing campaigns - Riggs, Thomas 1963-; Gale Group (Detroit, Mich. Gale, 2007)
An annual publication that profiles important marketing campaigns of the 20th century.
Electronic reproduction.
Keywords: Advertising campaigns -- United States -- History -- 20th century; Advertising campaigns -- United States -- History -- 21st century; Marketing -- United States -- History -- 20th century; Marketing -- United States -- History -- 21st century; Electronic books